MODEL PERMEABLE PAVEMENT,BIOSWALE DAN PLANTERS BOXES SEBAGAI MODEL PENGENDALIAN GENANGAN DI KAWASAN PERMUKIMAN PADAT KOTA MEDAN - Ina Triesna Budiana; Nurmaidah Nurmaidah (Universitas Medan Area, 2022)
The development of urban areas causes a lot of conversion of open land into housing and public facilities which reduces the absorption area causing flooding and inundation. When it rains heavily, the existing drainage channels are no longer able to accommodate runoff. To overcome this problem, one of the existing solutions is to implement an environmentally sound drainage system, namely the Green Infrastructures system where the drainage system is made in addition to accommodating runoff, it can also change the absorption area to be attractive or aesthetic for the area and store sufficient water reserves, namely with a drainage system model of Permeable Pavement, Planter Boxes and Bioswale which are adjusted to the conditions of the flood and inundation locations. The purpose of this research is the Green Infrastructures drainage system model will create an environmentally friendly spatial planning concept as well as a solution to overcome flooding and inundation in PB Selayang II Village, Medan Selayang District, Medan City. The research method used is descriptive quantitative with a positivistic approach to research. namely a scientific approach based on inductive reasoning. This approach requires certainty in a truth in the form of conclusions that can be measured, observed and verified (Moleong, 1999).